Faith Seeking Action Mission, Social Movements, and the Church in Motion. - Leffel, Gregory P. (Lanham : Scarecrow Press, 2007)
In Faith Seeking Action, author Gregory Leffel links a description of the church as a global movement with a description of contemporary social movements that are actively challenging today's societies, such as the environmental, global justice, and identity movements. Not surprisingly, Christian communities and communities of social activists share much in common as they each work to enrich their societies. It is natural then to ask what missionally-concerned Christians may learn from social movements about the public role of their churches, the connection of their beliefs to social change, a.
Cover Page; Title Page; Copyright Page; Dedication; Contents; List of Tables and Figures; Abbreviations and Acronyms; Series Foreword J. Steven O'Malley and Howard A. Snyder; Sub-Series Foreword Michael A. Rynkiewich; Introduction; 1 Mission and Movements; 2 Toward a Missio-Ecclesiology; 3 Social Movements: An Interpretive Framework; 4 The Antiglobalization Movement; 5 The Sanctuary Movement; 6 The Xenos Christian Fellowship House Church Movement; 7 Social Movements: An Action Framework; 8 Missio-Ecclesiology: Faith Seeking Action; 9 Mission and Imagination; Bibliography; Index.
About the Author.
Print version record.
Keywords: Mission of the church; Missions; Sociology, Biblical; Church and social problems; Social movements -- Religious aspects; Electronic books